CNT-Water Nanojet Impingement Cooling of a Sinusoidally Moving Isothermal Hot Wall - Selimefendigil, Fatih; Öztop, Hakan Fehmi (CRC Press, 2019)
Nanofluid technology was successfully used in a variety of thermal engineering applications such as in heat exchangers, refrigeration, renewable energy systems, thermal storage, and many others. Jet impingement cooling is another field where nanofluid technology was successfully implemented. This chapter examines fluid flow and heat transfer characteristics for carbon nanotube-water nanofluid double jet impingement cooling of a hot surface which has a sinusoidally varying velocity component. It analyses nanojet impingement cooling of a hot moving surface was numerically. Time-spatial average Nusselt number enhances linearly with solid particle volume fraction for all Strouhal numbers and Reynolds numbers in the case of sinusoidal varying hot wall. Numerical analysis of cooling of a corrugated hot surface with jet impingement was performed in reference. Effects of various nanoparticle solid volume fraction and various particle shapes on the convective heat transfer performances were examined. Nanofluid with single-walled carbon nanotube which has a higher thermal conductivity as compared to other convectional nanoparticles was considered. © 2020 by Taylor & Francis Group, LLC.